The making of a sociologist : between being and knowing - Goldthorpe, John H. (Routledge, 2025)
"This book offers a journey through the problems and the progress of the discipline of sociology in the UK and Europe throughout the second half of the twentieth century via an exploration of seven social settings from the life of a now eminent sociologist. It conceptualises the complex relation that exists between being and knowing, and between the personal knowledge that comes from lived experience and the essentially impersonal knowledge that any science seeks to pursue. The seven - very contrasting - settings are described in detail, together with reference to some of their leading personalities, such as David Glass, Karl Popper, Norbert Elias, Sebastian Sprott, Noel Annan, E. M. Forster, Gösta Rehn, Chelly Halsey, Fred Hirsch and Jürgen Habermas. In each case, the author shows how his lived experience within these settings formed a substratum of his sociology and how he navigated the line between personal knowledge as a creative resource and personal knowledge as bias using methodological discipline. It will ultimately appeal to those with interests in sociology, philosophy of science, sociological histories, and biographical methods"--